The co-management of tuberculosis-diabetes co-morbidities in Indonesia under the National Tuberculosis Control Program: results from a cross-sectional study from 2017 to 2019 - Weixi Jiang; Trimawartinah; Fauziah Mauly Rahman; Adik Wibowo; Adhi Sanjaya; Permata Imani Ima Silitonga; Shenglan Tang; Qian Long (BMC, 2022)
Abstract Background Indonesia suffers from a high burden of tuberculosis (TB) and diabetes (DM). The government initiated national TB-DM co-management activities under the National TB Control Program in 2017. This study investigates the detection and treatment outcomes of TB-DM in Jakarta after implementing these activities, and identifies the main factors associated with these outcomes. Methods A cross-sectional study was conducted using TB registry data in two districts of Jakarta, East Jakarta (low-income) and South Jakarta (high-income). A 5-step cascade analysis was used: diagnosed TB patients; TB patients tested for DM; diagnosed TB-DM patients; and patients received and completed TB treatment/cured. We conducted descriptive analyses to understand the characteristics of TB and TB-DM patients, and used a two-level mixed-effect logistic regression to explore factors associated with having a DM test and completing TB treatment/being cured. Results Over the study period (2017-2019) 50.8% of the new pulmonary TB patients aged over 15 were tested for DM. The percentage increased from 41.7% in 2017-2018 to 60.1% in 2019. Of the TB patients tested for DM, 20.8% were diagnosed with DM. Over 90% of the detected TB-DM patients received standard TB treatment, 86.3% of whom completed treatment/were cured. Patients in East Jakarta were more likely to be tested for DM and to complete standard TB treatment/be cured than patients in South Jakarta (P <  0.001). Bacteriologically positive TB patients were more likely to be tested for DM (OR = 1.37, 95% CIs 1.17,1.60). Patients diagnosed in sub-district level healthcare centers had a higher likelihood of being tested for DM than those in government and private hospitals (P <  0.05). Receiving DM treatment was associated with a higher likelihood of completing TB treatment/being cured (OR = 1.82, 95% CIs 1.20, 2.77). Conclusions TB-DM case detection significantly improved in 2019 after introducing TB-DM co-management activities in Jakarta, while gaps in TB-DM co-management existed between bacteriologically positive and clinically diagnosed TB patients, and across different types of health facilities. Collaboration between TB and DM departments should be strengthened, and more resources need to be mobilized to further improve the co-management of TB-DM in Indonesia.